43rd Fluid Dynamics Conference 2013
DOI: 10.2514/6.2013-2982
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Unsteadiness in a 2D Laminar Shock-Induced Separation Bubble

Abstract: A computational study of the interaction between an oblique shock-wave and a laminar boundary-layer on a flat plate is carried out to investigate the unsteady character of a two-dimensional (2D) separation bubble at a free-stream Mach number of 1.5. In order to validate the code, a review of the case is presented, highlighting some significant differences compared to previous works that were not run sufficiently far in time. A steady base flow is forced with white noise and a global analysis is carried out to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…In the present investigation of the interaction of an oblique shock wave and a laminar boundary layer, the simulation setup follows the experiments of Hakkinen et al 1 Skin friction and wall pressure at the plate are presented in figure 3 and are compared with results from Hakkinen et al, 1 Katzer 23 and Sandham et al 13,24 As expected, the results show rapid changes near the separation and reattachment and a pressure plateau in the bubble region. The pressure ratio reaches the value of 1.4 downstream of the reflected shock in accordance with the Rankine-Hugoniot relations.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…In the present investigation of the interaction of an oblique shock wave and a laminar boundary layer, the simulation setup follows the experiments of Hakkinen et al 1 Skin friction and wall pressure at the plate are presented in figure 3 and are compared with results from Hakkinen et al, 1 Katzer 23 and Sandham et al 13,24 As expected, the results show rapid changes near the separation and reattachment and a pressure plateau in the bubble region. The pressure ratio reaches the value of 1.4 downstream of the reflected shock in accordance with the Rankine-Hugoniot relations.…”
Section: Resultsmentioning
confidence: 63%
“…23, 24 Katzer 23 also obtained a longer bubble than in the experiments, however it is shorter than ours and those from other recent two-dimensional numerical calculation. The reasons for these differences have been investigated recently by Sansica et al 13 They also studied the effect of using different models for calculating the viscosity as a function of temperature on the bubble length. They concluded that the different methods used to calculate the viscosity does not affect the bubble length.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…To validate the code implementation, comparison to the reference solution published in [1] was performed. A (609 × 255) grid stretched in the wall normal x 1 direction was used, with length L x1 and stretch factor β as…”
Section: Resultsmentioning
confidence: 99%
“…Shock-wave/boundary-layer interactions (SBLI) are a significant factor in the consideration of transonic/supersonic aircraft designs, with the induced adverse pressure gradients leading to detrimental boundary-layer thickening and separation of the flow. Recent studies of laminar SBLI include [1], [2], the first of which was simulated in the legacy Fortran code 'SBLI'. OpenSBLI [3] is a modern Python-based 'future-proof' version of the SBLI code, generating C code tailored to a user specified problem; the symbolic algebra library SymPy is used extensively throughout.…”
Section: Introductionmentioning
confidence: 99%